2004
DOI: 10.1063/1.1825615
|View full text |Cite
|
Sign up to set email alerts
|

As-doped p-type ZnO produced by an evaporation∕sputtering process

Abstract: Strongly p-type ZnO is produced by the following sequence of steps: (1) evaporation of Zn3As2 on a fused-quartz substrate at 350°C; and (2) sputtering of ZnO with substrate held at 450°C. The electrical characteristics include: resistivity of 0.4Ωcm, a mobility of 4cm2∕Vs, and a hole concentration of about 4×1018cm−3. This resistivity is among the best (lowest) ever reported for p-type ZnO. Secondary-ion mass spectroscopic analysis gives an average As concentration about 5×1019cm−3, and a simple one-band fit o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(130 citation statements)
references
References 33 publications
7
120
0
3
Order By: Relevance
“…This issue is of particular relevance, since it has been reported that not more than 5-13% of incorporated As can be electrically activated in ZnO [4,5,7]. The maximum concentration of As in our implanted sample (around 7.6×10 18 cm −3 ) is comparable with the As concentration used in most other studies.…”
Section: Relevance Of Current Results With Respect To the Acceptor Mosupporting
confidence: 70%
See 1 more Smart Citation
“…This issue is of particular relevance, since it has been reported that not more than 5-13% of incorporated As can be electrically activated in ZnO [4,5,7]. The maximum concentration of As in our implanted sample (around 7.6×10 18 cm −3 ) is comparable with the As concentration used in most other studies.…”
Section: Relevance Of Current Results With Respect To the Acceptor Mosupporting
confidence: 70%
“…In the case of the technologically promising II-VI compound ZnO, besides N [1,2] the heavy group-V elements P [1,2], As [2][3][4][5][6][7][8][9], and Sb [10][11][12] have been reported in the literature as possible p-type dopants. However, there is an ongoing debate whether for P, As, and Sb the p-type character results from these impuritities simply replacing O atoms, thus acting as simple "chemical" dopants [3,4,8], or is due to the formation of more complicated defect complexes [9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The realization of p-type ZnO has proven difficult due to its asymmetric doping limitations. 5 Fortunately, thanks to the considerable worldwide efforts, various elements have been used as p-type dopants for ZnO, such as N, 6-8 P, 9 As, 10 and Li. 11 However, it is the inexplicit p-type doping mechanism as well as the stability and reproducibility problems that become the bottleneck in the development of ZnO devices.…”
mentioning
confidence: 99%
“…Áàãàòî äîñë³äíèê³â âèâ÷àëè åëåêòðè÷í³ îì³÷í³ êîíòàêòè íà ZnO [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Îäíàê, ùî ñòî-ñóºòüñÿ äîñë³äaeåíü åëåêòðè÷íèõ êîíòàêò³â íà Zn 1-x Mn x O, íàñê³ëüêè íàì â³äîìî ç ë³òåðàòóðè, íå ïðîâîäèëîñÿ.…”
Section: âñòóïunclassified